The Role of Trust in Understanding the Impact of Social Media Marketing on Brand Equity and Brand Loyalty - Ayyub, Muhammad Furqan; Asghar, Adnan; Arshad, Hafiz Muhammad Jawad (Archives of Business Research, 2022)
.